ANALYSIS OF TESTING OF WEB BASED E-RAPORT INFORMATION SYSTEMS USING BLACK BOX AND WHITE BOX METHODS - Trivani, Ovie Julian; Winanda , Aziza Femi; Wahyuni, Dinni; Dieta , Dekra Wond Dwi Putra; Sihite, Ari Parulian; Rizki, Muhammad (Lembaga Riset dan Inovasi Almatani, 2025)
An online tool called e-report is utilized to process students' final grades. For SMP 4 Muhammadiyah Pekanbaru pupils, manual delivery methods like regular paper and report cards are still used for information submission and checking marks on report cards. A website-based report card application was developed in order to make it simpler for students at SMP Muhammadiyah 4 Pekanbaru to view grades and obtain information on report cards by utilizing existing technology and computerization. The author offers using the e-report as a solution to the issue. The authors employ the agile technique, which is a development model that is carried out iteratively, repeatedly, and can experience modifications as needed, in order to create and build the report card system.